1986
DOI: 10.1063/1.337117
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-enhanced growth and composition of silicon oxynitride films

Abstract: Silicon oxynitride films with varying oxygen/nitrogen ratio were grown from SiH4, N2O, and NH3 by means of a plasma-enchanced chemical vapor deposition process. The elemental composition of the deposited films was measured by a variety of high-energy ion beam techniques. To determine the chemical structure we used Fourier transform infrared absorption spectroscopy and electron-spin resonance. Ellipsometric data and values for mechanical stress are also reported. We show that the entire range of compositions fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
1
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(39 citation statements)
references
References 19 publications
6
29
1
1
Order By: Relevance
“…21 For SiO x N y H z films, many authors find a dominant absorption band, with a single maximum located at intermediate frequencies between those of SiO 2 and Si 3 N 4 . 1,[11][12][13]30,45,46 This behavior is characteristic of singlephase homogeneous SiO x N y H z and its bonding structure is well described by the RBM previously explained ͓see Eq. ͑3͔͒.…”
mentioning
confidence: 75%
“…21 For SiO x N y H z films, many authors find a dominant absorption band, with a single maximum located at intermediate frequencies between those of SiO 2 and Si 3 N 4 . 1,[11][12][13]30,45,46 This behavior is characteristic of singlephase homogeneous SiO x N y H z and its bonding structure is well described by the RBM previously explained ͓see Eq. ͑3͔͒.…”
mentioning
confidence: 75%
“…1,2 One of the most extended techniques for the deposition of silicon oxynitride films ͑in the following SiO x N y H z ) at low temperatures is plasma enhanced chemical vapor deposition ͑PECVD͒, [3][4][5] with the remote PECVD 1,6,7 or electron cyclotron resonance ͑ECR-PECVD͒ [8][9][10][11] variants. While these techniques meet the low thermal budget requirement, the quality of the as-deposited dielectric films is not as good as that of thermally grown SiO 2 films.…”
Section: Introductionmentioning
confidence: 99%
“…Like others [26,27] we assume that the presence of N-N, O-O, H-H and N-O bonds in SiON can be excluded due to the high bond strength in N 2 , O 2 , H 2 and NO molecules, respectively. Also our XPS studies have shown no evidence for N-N and N-O bonds in the layers.…”
Section: Properties Of Optimized Sion Layersmentioning
confidence: 99%